Cervical spine injuries prevention in elite male rugby players: an electromyographic study on neck muscles activity - Demeco, A.; de Sire, A.; Marotta, N.; Salerno, A.; Bartocci, G.; Frizziero, A.; Paermi, S.; Tanrögen, B.; Renzi, F.; Ammendolia, A.; Costantino, C. (The Journal of Sports Medicine and Physical Fitness, 2026)
BACKGROUND: Rugby is a high-contact sport with a significant injury risk, particularly cervical spine trauma. The repeated mechanical overload can contribute to long-term cervical dysfunctions. Surface electromyography (sEMG) and inertial sensors (IMU) offer valuable insights into neuromuscular function.